ARCHITECTURE AND WELL BEING IN INFORMAL SETTLEMENTS IN SURABAYA - Regan Potangaroa; Happy Ratna Santosa; Hasian Siregar (Journal of Architecture&ENVIRONMENT, 2011)
The aim of this paper is to “explore and to highlight the human dimensions in solving the problem of low income housing and settlement; not only from the political, economic or social as such but from the human and humane perspectives”. And with this in mind this paper sets out to ascertain what aspects of architecture contribute to the well being (happiness) of people in informal settlements?